Mechanism and Substrate Recognition of Human Holo ACP Synthase - Bunkoczi, Gabor (Elsevier, 2007)
Mammals utilize a single phosphopantetheinyl transferase for the posttranslational modification of at least three different apoproteins: the carrier protein components of cytosolic and mitochondrial fatty acid synthases and the aminoadipate semialdehyde reductase involved in lysine degradation. We determined the crystal structure of the human phosphopantetheinyl transferase, a eukaryotic phosphopantetheinyl transferase characterized, complexed with CoA and Mg(2+), and in ternary complex with CoA and ACP. The involvement of key residues in ligand binding and catalysis was confirmed by mutagenesis and kinetic analysis. Human phosphopantetheinyl transferase exhibits an α/β fold and 2-fold pseudosymmetry similar to the Sfp phosphopantetheinyl transferase from Bacillus subtilis. Although the bound ACP exhibits a typical four-helix structure, its binding is unusual in that it is facilitated predominantly by hydrophobic interactions. A detailed mechanism is proposed describing the substrate binding and catalytic process.